2010
DOI: 10.1152/jn.00911.2009
|View full text |Cite
|
Sign up to set email alerts
|

Varying Overall Sound Intensity to the Two Ears Impacts Interaural Level Difference Discrimination Thresholds by Single Neurons in the Lateral Superior Olive

Abstract: The lateral superior olive (LSO) is one of the earliest sites in the auditory pathway involved in processing acoustical cues to sound location. LSO neurons encode the interaural level difference (ILD) cue to azimuthal location. Here we investigated the effect of variations in the overall stimulus levels of sounds at the two ears on the sensitivity of LSO neurons to small differences in ILDs of pure tones. The neuronal firing rate versus ILD functions were found to depend greatly on the overall stimulus level, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 49 publications
5
52
0
Order By: Relevance
“…Collectively, the half-maximal ILD, ILD dynamic range, and rate-ILD slope capture the attributes of a neuron's response that, together with spike variance, determine its capacity to encode ILD (Tollin et al 2008;Tsai et al 2010; see also Fig. 3).…”
Section: Neurophysiological Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Collectively, the half-maximal ILD, ILD dynamic range, and rate-ILD slope capture the attributes of a neuron's response that, together with spike variance, determine its capacity to encode ILD (Tollin et al 2008;Tsai et al 2010; see also Fig. 3).…”
Section: Neurophysiological Methodsmentioning
confidence: 99%
“…To facilitate analysis over a broad range of continuously varying ILDs, the fitted sigmoid function relating spike count to ILD (see above) was used to compute y=(ILD) for each neuron. Then, the ILD-dependent variance [(ILD) 2 ] for each neuron was approximated by fitting a two-parameter power function of the form y ϭ ax b , where x is spike count and a and b are free parameters (Tsai et al 2010). Across the ILD-sensitive neurons (n ϭ 103), the variance vs. spike count data were well described by the power function (mean R 2 ϭ 0.89 Ϯ 0.1).…”
Section: Statistical Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been shown that neurons in the auditory cortex are level tolerant when encoding horizontal and vertical sound locations (Zhou and Wang 2012). Other physiological studies have demonstrated that certain neurons in the inferior colliculus and the auditory cortex maintain their spatial sensitivity at high sound levels (Irvine and Gago 1990;Miller and Recanzone 2009), whereas the sensitivity of neurons in the lateral superior olive decreases with sound level (Tsai et al 2010), although these studies only examined sound localization in azimuth.…”
Section: Discussionmentioning
confidence: 99%